School Development Plan in SD IT Al-Ihsan Baleendah Bandung - Asy’ari, Lutfi; Nurseha, Alamsyah; Muslihah, Neni Nadiroti; Mutaqin, Ejen Jenal (Universitas Sebelas Maret, 2021)
Planning is carried out not only to solve the problems at hand, but also to plan ahead in terms of improving school performance or to anticipate changes and demands of the times. In general, schools prioritize physical development, even though non-physical development is much more important, because one of the main goals of schools is to produce quality students. Planning can be distinguished based on the time period, including long-term planning, medium-term planning, and short-term planning. In this regard, strategic planning plays an important role in achieving the targets of education providers in the midst of competition. The focus of this research is the school development plan at SDIT Al-Ihsan Baleendah. This study aims to capture the school development plan carried out by SDIT Al-Ihsan Baleendah. This type of research is a qualitative descriptive study. In the data collection technique, various techniques were used in this study, namely interviews, observation and documentation. The data analysis procedure used in this study was qualitative analysis. Based on the findings from the research results, it was concluded that development planning at SDIT Al-Ihsan Baleendah was carried out with the baseline analysis stage, forming a vision and mission, translating it into strategic planning and operational plans.